Influence of the substitution of Mn-site on the properties of the La0.67Ca0.33Mn0.9A0.4 (A=Ni, Al, Cu) compounds - Nguyen, Tuan Anh; nguyen, Sinh Huy; tran, THo Dinh; Do, Thang Viet (VNU Journal of Science: Mathematics - Physics, 2017)
Abstracts